Communication: A Tool for Marriage Stability - Ibe, Anthony Chiwuba (Studia Bioethica, 2015)
The Holy Father Pope Francis believes that it is always possible to keep alive and stable the bond of marriage, which has its foundation in God and thus overcome the “culture of the provisory”. This paper presents communication as a salient tool by which peace and stability could be achieved in marriage relationships. Communication could be verbal or emotional. The language of spousal love is a tool. And as such could be put into good or bad use. It can be perfected by faithfulness and/or disordered by sin because of infidelity. If the spousal corporeal language is in action but the intention and the mind of the spouses do not express this gesture, they have empty gesture of love – a false love and a false historical kiss that signifies betrayal and not love (Cf. the kiss of Judas to Jesus).